Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F.; Gouveia, Célia; Mériaux, Catherine; et al. (Agricultural and Forest Meteorology, 2014)
This study details the physiological responses of cork oak (Quercus suber L.) to manipulated water inputs. Treatments named as dry, ambient and wet, which received 80, 100 and 120% of the annual precipitation, respectively, were applied to a Mediterranean woodland in southern Portugal. Tree ecophysiology and growth were monitored from 2003 to 2005. The impacts of the water manipulation were primarily observed in tree transpiration, especially dur- ing summer drought. Rainfall exclusion reduced the annual stand canopy transpiration by 10% over the 2-year study period, while irrigation increased it by 11%. The accumulated tree transpiration matched precipitation in spring 2004 and 2005 at the stand level, suggesting that cork oak trees rely on precip- itation water sources during the peak of the growing season. However, during the summer droughts, by trees appeared unaffected by the extreme drought of 2005. Our study shows that cork oak rapidly and completely recovered from the extreme dry year of 2005 or from rainfall exclusion. Our results support the eco-hydrological equilibrium theory by which plant acquire complementary protective mechanisms to buffer the large variability in water availability experienced in semi-arid ecosystems. In optimizing their structural biomass increase in response to increasing drought stress, cork oak trees succeeded in restricting water losses to maintain the minimum leaf water potential above the critical threshold of xylem embolism, though with narrower hydraulic safety margins in 2005. Our findings highlight cork oak’s sensitivity to the amount and timing of late spring precipitation. This could be critical as future climate scenarios predict a reduction of spring precipitation as well as enhanced severity of droughts in the Iberian Peninsula by the end of the 21st century. In inducing water stress before the onset of summer droughts, the predicted spring precipitation decline could drive the species closer to the threshold of catastrophic xylem embolism at the peak of the drought period. groundwater was the main water source for trees. Despite the significant differences in soil water content and tree transpiration, no treatment effects could be detected in leaf water potential and leaf gas exchange, except for a single event after spring irri- gations in the very dry year 2005. These irrigations were intentionally delayed to reduce dry spell duration during the peak of tree growing season. They resulted in an acute positive physiological response of trees from the wet treatment one week after the last irrigation event leading to a 32% raise of stem diame- ter increment the following months. Our results suggest that in a semi-arid environment precipitation changes in spring (amount and timing) have a stronger impact on cork oak physiology and growth than an overall change in the total annual precipitation. The extreme drought of 2005 had a negative impact on tree growth. The annual increment of tree trunk diameter in the ambient and dry treatments was reduced, while it increased for trees from the wet treatment. Water shortage also significantly reduced leaf area. The latter dropped by 10.4% in response to the extreme drought of 2005 in trees from the ambient treatment. The reduction was less pronounced in trees of the wet treatment (−7.6%), and more pronounced in trees of the dry treatment (−14.7%). Cork oak showed high resiliency to inter-annual precipitation variability. The annual accumulated tree transpiration, the minimum midday leaf water potential and the absolute amount of groundwater used
From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Gas exchange; Precipitation change; Quercus suber; Soil moisture; Throughfall manipulation; Tree transpiration

Decreased rates of terpene emissions in Ornithopus compressus L. and Trifolium striatum L. by ozone exposure and nitrogen fertilization. - Llusia, Joan; Bermejo-Bermejo, Victoria; Calvete-Sogo, Héctor; Penuelas, Josep (Environmental pollution (Barking, Essex : 1987), 2014)
Increasing tropospheric ozone (O3) and nitrogen soil availability (N) are two of the main drivers of global change. They both may affect gas exchange, including plant emission of volatiles such as terpenes. We conducted an experiment using open-top chambers to analyze these possible effects on two leguminous species of Mediterranean pastures that are known to have different O3 sensitivity, Ornithopus compressus and Trifolium striatum. O3 exposure and N fertilization did not affect the photosynthetic rates of O. compressus and T. striatum, although O3 tended to induce an increase in the stomatal conductance of both species, especially T. striatum, the most sensitive species. O3 and N soil availability reduced the emission of terpenes in O. compressus and T. striatum. If these responses are confirmed as a general pattern, O3 could affect the competitiveness of these species.
Keywords: Annual pastures; BVOCS; Emissions; Gas exchange; legumes; Nitrogen deposition; Ozone; terpenes

Drought stress does not protect Quercus ilex L. from ozone effects: results from a comparative study of two subspecies differing in ozone sensitivity - Alonso, R; Elvira, S; González-Fernández, I; Calvete, H; García-Gómez, H; Bermejo, V (Plant Biology, 2014)
Long-term effects of ozone (O3) exposure and drought stress were assessed on two subspecies of Quercus ilex: ssp. ilex and ssp. ballota. Two-year-old seedlings were continuously exposed for 26 months in open-top chambers to three O3 treatments: charcoal filtered air, non-filtered air and non-filtered air supplemented with 40 nl·l−1 O3. Additionally, two irrigation regimes were adopted: half of the plants were well-watered and the others received half of the water supplied to control plants. Growth, shoot water potential and gas exchange rates were assessed seasonally, and biomass accumulation was determined at the end of the experiment. Drought stress caused higher reductions of gas exchange, growth and biomass accumulation than O3 exposure in both subspecies. The combination of O3 and drought stress caused further decreases of accumulated aboveground biomass but no additive effects were observed on gas exchange rates or root biomass. Thus, drought stress did not protect Q. ilex from O3 effects on biomass when the response of the whole plant was considered. Q. ilex ssp. ballota was more sensitive to O3 and ssp. ilex was more affected by drought stress. The different O3 sensitivity was not only related to pollutant uptake but also to the ability of plants for resource acquisition and allocation. Based on biomass dose–response functions, Q. ilex is more resistant to O3 than other European evergreen tree species, however, O3 represents an additional stress factor that might be impairing plant ability to withstand current and future climate change.
Keywords: evergreen broadleaf mediterranean; Evergreen broadleaf Mediterranean vegetation; Gas exchange; Growth; Holm oak; ozone response functions; Vegetation

Non-invasive tools to estimate stress-induced changes in photosynthetic performance in plants inhabiting Mediterranean areas - Guidi, Lucia; Calatayud, Angeles (Environmental and Experimental Botany, 2013)
In Mediterranean areas, plants are concomitantly exposed to various abiotic stresses such as light intensity, water deficit, extremes in air temperature, air pollutants, etc. These environmental pressures adversely affect plant development. Changes in photosystem activity are an early response of plants to abiotic stresses. Therefore, chlorophyll (Chl) fluorescence and gas exchange, two non-invasive, rapid and inexpensive techniques for measuring photosynthesis in leaves, have been widely used by plant ecophysiologists to analyse plant responses to stressful conditions. Chl a fluorescence and gas exchange parameters can be indeed used to evaluate changes in photochemical and non-photochemical processes in photosystems associated with electron transport, CO2 fixation, and heat dissipation. In this review, we focus our analysis on the effects of different abiotic stresses on the photochemistry of Mediterranean plants using Chl a fluorescence and gas exchange measurements. Since changes in photosynthetic parameters are observed in the absence of visual injuries, these methodologies constitute fundamental tools to predict and evaluate the extent to which abiotic stresses damage photosynthesis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Abiotic stress; Chlorophyll a fluorescence; climate change; Gas exchange; Oxidative stress; photosynthesis

Nitrogen dioxide (NO2) uptake by vegetation controlled by atmospheric concentrations and plant stomatal aperture - Chaparro-Suarez, I. G.; Meixner, F. X.; Kesselmeier, J. (Atmospheric Environment, 2011)
Nitrogen dioxide (NO2) exchange between the atmosphere and ﬁve European tree species was investigated in the laboratory using a dynamic branch enclosure system (consisting of two cuvettes) and a highly speciﬁc NO2 analyzer. NO2 measurements were performed with a sensitive gas phase chemiluminescence NO detector combined with a NO2 speciﬁc (photolytic) converter, both from Eco-Physics (Switzerland). This highly speciﬁc detection system excluded bias from other nitrogen compounds. Investigations were performed at two light intensities (Photosynthetic Active Radiation, PAR, 450 and 900 mmol m2 s 1 ) and NO2 concentrations between 0 and 5 ppb. Ambient parameters (air temperature and relative humidity) were held constant. The data showed dominant NO2 uptake by the respective tree species under all conditions. The results did not conﬁrm the existence of a compensation point within a 95% conﬁdence level, though we cannot completely exclude emission of NO2 under very low atmospheric concentrations. Induced stomatal stricture, or total closure, by changing light conditions, as well as by application of the plant hormone ABA (Abscisic Acid) caused a corresponding decrease of NO2 uptake. No loss of NO2 to plant surfaces was observed under stomatal closure and species dependent differences in uptake rates could be clearly related to stomatal behavior
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Deposition; Gas exchange; Nitrogen dioxide; Stomatal uptake; Vegetation

Root hydraulic conductance, gas exchange and leaf water potential in seedlings of Pistacia lentiscus L. and Quercus suber L. grown under different fertilization and light regimes - Hernández, E I; Vilagrosa, A; Luis, V C; Llorca, M; Chirino, E; Vallejo, V R (Environmental and Experimental Botany, 2009)
Differences in morphology, biomass allocations and physiological responses were investigated in seedlings of Mastic tree (Pistacia lentiscus L.) and Cork oak (Quercus suber L.) submitted to contrasting fertilization and light regimes during early growth. These species are two evergreen sclerophyllous Mediterranean species frequently used in Mediterranean reforestation programmes. Fertilization was the treatment that affected most of the morphological and physiological variables evaluated in P. lentiscus and Q. suber seedlings. Leaf area and speciﬁc leaf area (SLA) were affected by shading treatment in both species, showing higher values in seedlings grown under shade. P. lentiscus seedlings showed a high capacity to modify root morphological variables and root hydraulic conductance (KR) with the fertilization treatment. In contrast, Q. suber showed low to moderate root system changes with the treatments applied, although the fertilization level affected biomass allocation (i.e., root to shoot ratio) in both species. Under high water demand, P. lentiscus seedlings with high KR allowed transpiration (E) to increase without increasing the water potential gradient between soil and leaves. In Q. suber, high fertilization induced signiﬁcant increases in photosynthesis (A), as well as a tendency to increase E with signiﬁcantly lower leaf water potential ( L)
Keywords: Drought; fertilization; Gas exchange; light; Root hydraulic conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Thermal optima of photosynthetic functions and thermostability of photochemistry in cork oak seedlings - Ghouil, Hana; Montpied, Pierre; Epron, Daniel; Ksontini, Mustapha; Hanchi, Belkacem; Dreyer, Erwin (Tree Physiology, 2003)
Temperature effects on photosynthesis were studied in seedlings of evergreen Mediterranean cork oak (Quercus suber L.). Responses to changes in temperature and the temperature optima of maximal carboxylation rate (Vcmax) and maximal light-driven electron flux (Jmax) were estimated from gas exchange measurements and a leaf-level photosynthesis model. The estimated temperature optima were approximately 34 and 33 °C for Vcmax and Jmax, respectively, which fall within the lower range of temperature optima previously observed in deciduous tree species. The thermostability of the photosynthetic apparatus was estimated according to the temperature at which basal chlorophyll a fluorescence begins to increase (Tc). The Tc was highly variable, increasing from 42 to 51 °C when ambient temperature rose from 10 to 40 °C, and increasing from 44 to 54 °C with decreasing soil water availability while net CO2 assimilation rate dropped to almost zero. When a heat shock was imposed, an additional small increase in Tc was observed in drought-stressed and control seedlings. Maximal Tc values following heat shock were about 56 °C, which, to our knowledge, are the highest values that have been observed in tree species. In conclusion, the intrinsic temperature responses of cork oak did not differ from those of other species (similar Tc under ambient temperature and water availability, and relatively low thermal optima for photosynthetic capacity in seedlings grown at cool temperatures). However, the large ability of cork oak to acclimate to drought and elevated temperature may be an important factor in the tolerance of this evergreen Mediterranean species to summer drought and high temperatures.
10.1093/treephys/23.15.1031
Keywords: chlorophyll fluorescence; Gas exchange; maximal carboxylation rate; maximal light-driven electron flow; Regeneration

Thermal optima of photosynthetic functions and thermostability of photochemistry in cork oak seedlings - Ghouil, Hana; Montpied, Pierre; Epron, Daniel; Ksontini, Mustapha; Hanchi, Belkacem; Dreyer, Erwin (Tree Physiology, 2003)
Temperature effects on photosynthesis were studied in seedlings of evergreen Mediterranean cork oak (Quercus suber L.). Responses to changes in temperature and the temperature optima of maximal carboxylation rate (Vcmax) and maximal light-driven electron flux (Jmax) were estimated from gas exchange measurements and a leaf-level photosynthesis model. The estimated temperature optima were approximately 34 and 33 °C for Vcmax and Jmax, respectively, which fall within the lower range of temperature optima previously observed in deciduous tree species. The thermostability of the photosynthetic apparatus was estimated according to the temperature at which basal chlorophyll a fluorescence begins to increase (Tc). The Tc was highly variable, increasing from 42 to 51 °C when ambient temperature rose from 10 to 40 °C, and increasing from 44 to 54 °C with decreasing soil water availability while net CO2 assimilation rate dropped to almost zero. When a heat shock was imposed, an additional small increase in Tc was observed in drought-stressed and control seedlings. Maximal Tc values following heat shock were about 56 °C, which, to our knowledge, are the highest values that have been observed in tree species. In conclusion, the intrinsic temperature responses of cork oak did not differ from those of other species (similar Tc under ambient temperature and water availability, and relatively low thermal optima for photosynthetic capacity in seedlings grown at cool temperatures). However, the large ability of cork oak to acclimate to drought and elevated temperature may be an important factor in the tolerance of this evergreen Mediterranean species to summer drought and high temperatures.
10.1093/treephys/23.15.103110.1093/treephys/23.15.1031
Keywords: chlorophyll fluorescence; Gas exchange; maximal carboxylation rate; maximal light-driven electron flow; Regeneration

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. - Gulías, J; Flexas, J; Abadía, A; Madrano, H (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]
Keywords: chlorophyll fluorescence; deciduous; Drought; evergreen; Gas exchange; leaf mass area; nitrogen; Pistacia; Quercus; Rhamnus; xanthophyll cycle

Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R.; Schäfer, L.; Gerlach, C. (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex

Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R; Schafer, L; Gerlach, C (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex

Photosynthesis and photoprotection in Quercus ilex resprouts after fire - Fleck, I; Hogan, K P; Llorens, L; Abadía, A; Aranda, X (Tree Physiology, 1998)
Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency of photosystem II (PSII), nonphotochemical quenching of chlorophyll fluorescence (NPQ), and the de-epoxidation of violaxanthin to zeaxanthin were also similar among leaves of different ages and treatments. In late July, photosynthetic rates and stomatal conductances were much greater in resprouts on the burned areas than in unburned plants. From early to late July, unburned plants showed an increase in NPQ and the de-epoxidation of violaxanthin to zeaxanthin, indicating increased photoprotection as a result of enhanced nonradiative dissipation of excess light energy. Plants on the burned plots did not show these changes. Leaves of all ages and treatments showed no substantial reduction in potential quantum yield of PSII (Fv/Fm) at midday or predawn, indicating that there was little or no photoinhibition. Leaf nitrogen and soluble protein contents varied with leaf age during July, but did not vary between treatments. We conclude that the primary effect of burning is an increase in water availability to resprouting plants that eliminates the need for photoprotection, at least in the short term. The decrease in photosynthetic rates of unburned leaves in late July was the result of reduced stomatal conductance. We suggest that lowered stomatal conductance is the primary limiting factor in Q. ilex leaves, governing the regulation of carboxylation activity and energy dissipation processes.
10.1093/treephys/18.8-9.607
Keywords: chlorophyll fluorescence; Gas exchange; Holm oak; photoinhibition; Photosystem II; zeaxanthin

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J. D. (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J D (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds

Photochemical reflectance index and leaf photosynthetic radiation-use-efficiency assessment in Mediterranean trees - Penuelas, J; Llusia, J; Piñol, J; Filella, I (International Journal of Remote Sensing, 1997)
Abstract This Letter presents new data validating the use of the photochemical reflectance index PRI (R570-R531)/(R570 + R531) to assess photosynthetic- radiation-use-efficiency under mild water stress. Gas exchange, fluorescence and the PRI of leaves from the Mediterranean trees Quercus ilex and Phillyrea latifolia growing in the field were followed from spring to summer 1996 in central Catalonia (NE Spain). The same variables were measured in seedlings of these two species and Pistacia lentiscus submitted to progressive drying after witholding irrigation. Except for severely drought damaged plants, significant relations of the reflectance index PRI with fluorescence yield of the photosystem II (Delta F/F' m), non photochemical fluorescence quenching ( qN ) and photosynthetic radiation use efficiency (PRUE) were found, thus indicating a functional relation among these parameters. A simple portable radiometer measuring ground level reflectance at narrow bands centred at 531 and 570nm could instantaneously calculate the PRI index and give the PRUE estimation.
doi: 10.1080/014311697217387
Keywords: Fluorescence (voyant); Gas exchange; photochemical reflectance index PRI; photosynthetic radiation use efficiency

Carbon isotope discrimination in Quercus ilex resprouts after fire and tree-fell - Fleck, Isabel; Grau, Daniel; Sanjose, M.; Vidal, D. (Oecologia, 1996)
Ecophysiological differences related to photo- synthesis were compared in holm oak Quercus ilex leaves from undisturbed holm-oak vegetation, resprouts after fire and resprouts after tree-fell. No significant dif- ferences in any parameter measured were observed be- tween the two kinds of resprout throughout the first growing season following disturbance. Resprouting leaves showed lower carbon isotope discrimination (A) and intercellular CO 2 concentration (Pi), and higher pho- tosynthesis, leaf conductance and transpiration rates than leaves from undisturbed stands. Nitrogen, soluble protein content and ribulose bisphosphate carboxylase (RuBP- Case) activity were 88%, 96% and 45% higher respec- tively, in both kinds of resprout. The results indicate that photosynthetic capacity, rather than stomatal conduc- tance, is the limiting factor in photosynthesis in re- sprouts. Chlorophyll content and chlorophyll a/b ratio did not differ between resprouts and undisturbed leaves, indicating that the observed differences were not a result of differences in light environment during leaf develop- ment. Leaf mass per area (LMA), was 80% higher in the resprouts, and was negatively related (r= -0,86) to A and positively related (r=0.87) to N content. Enhanced car- bon assimilation after disturbances resulted in higher wa- ter use efficiency, as indicated by lower A values in the resprouts. We conclude that the cause of defoliation was not relevant in the physiology of the resprouts, suggest- ing the importance of underground organs.
Keywords: carbon isotope discrimination; Fire and tree-fell resprouts; Gas exchange; RuBPCase activity

Carbon isotope discrimination in Quercus ilex resprouts after fire and tree-fell - Fleck, Isabel; Grau, Daniel; Sanjosé, M; Vidal, D (Oecologia, 1996)
Ecophysiological differences related to photo- synthesis were compared in holm oak Quercus ilex leaves from undisturbed holm-oak vegetation, resprouts after fire and resprouts after tree-fell. No significant dif- ferences in any parameter measured were observed be- tween the two kinds of resprout throughout the first growing season following disturbance. Resprouting leaves showed lower carbon isotope discrimination (A) and intercellular CO 2 concentration (Pi), and higher pho- tosynthesis, leaf conductance and transpiration rates than leaves from undisturbed stands. Nitrogen, soluble protein content and ribulose bisphosphate carboxylase (RuBP- Case) activity were 88%, 96% and 45% higher respec- tively, in both kinds of resprout. The results indicate that photosynthetic capacity, rather than stomatal conduc- tance, is the limiting factor in photosynthesis in re- sprouts. Chlorophyll content and chlorophyll a/b ratio did not differ between resprouts and undisturbed leaves, indicating that the observed differences were not a result of differences in light environment during leaf develop- ment. Leaf mass per area (LMA), was 80% higher in the resprouts, and was negatively related (r= -0,86) to A and positively related (r=0.87) to N content. Enhanced car- bon assimilation after disturbances resulted in higher wa- ter use efficiency, as indicated by lower A values in the resprouts. We conclude that the cause of defoliation was not relevant in the physiology of the resprouts, suggest- ing the importance of underground organs.
Keywords: carbon isotope discrimination; Fire and tree-fell resprouts; Gas exchange; RuBPCase activity

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I.; Grau, D.; Sanjose, M.; Vidal, D. (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I; Grau, D; Sanjosé, M; Vidal, D (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell